2021
DOI: 10.3390/cells10051045
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle Surface Signatures in IPF Patients: A Multiplex Bead-Based Flow Cytometry Approach

Abstract: Background: Extracellular vesicles (EVs) are secreted by cells from their membrane within circulation and body fluids. Knowledge of the involvement of EVs in pathogenesis of lung diseases is increasing. The present study aimed to evaluate the expression of exosomal surface epitopes in a cohort of idiopathic pulmonary fibrosis (IPF) patients followed in two Italian Referral Centres for Interstitial Lung Diseases, comparing them with a group of healthy volunteers. Materials and Methods: Ninety IPF patients (medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…In addition, increased expression of CD8 was associated with poor prognosis in IPF in survival analysis. These results provide the basis for the use of blood exosome surface epitopes as candidate biomarkers for the diagnosis and prognosis of IPF ( D'Alessandro et al, 2021 ).…”
Section: Exosomes As Biomarkers Of Pfmentioning
confidence: 90%
“…In addition, increased expression of CD8 was associated with poor prognosis in IPF in survival analysis. These results provide the basis for the use of blood exosome surface epitopes as candidate biomarkers for the diagnosis and prognosis of IPF ( D'Alessandro et al, 2021 ).…”
Section: Exosomes As Biomarkers Of Pfmentioning
confidence: 90%
“…To our knowledge, only one paper investigates the expression of exosomal surface markers in serum from IPF patients [48]. The authors found an increase in the expression of CD19, CD8, CD69 and CD86 in such patients, suggesting and confirming the "immune profile" of IPF pathogenesis.…”
Section: Evs In Peripheral Blood From Ild Patientsmentioning
confidence: 92%
“…They also reported high expression of ROR1, a key mediator of WNT5a signalling, on EVs. WNT5a signalling is a regulator of fibroblast proliferation and resistance to apoptosis, both mechanisms involved in the development and progression of lung fibrosis in IPF [48].…”
Section: Evs In Peripheral Blood From Ild Patientsmentioning
confidence: 99%
“…A growing body of literature shows that EVs are a key component in the pathobiology of IPF. Those vesicles accumulate in the lungs of patients with IPF [ 164 ], and they harbor specific cargoes of proteins and microRNA [ 164 , 165 , 166 , 167 , 168 , 169 ]. Mechanistically, fibrosis-derived EVs activate the mechanism of fibrosis, such as fibroblast proliferation and activation, by controlling developmental signaling such as Wnt or TGF-β1 [ 164 , 167 ].…”
Section: Extracellular Lipids As Important Regulators Of Fibrosis Pro...mentioning
confidence: 99%